Transkulturelle Kunstvermittlung: Zum Bildungsgehalt ästhetisch-künstlerischer Praxen - Eremjan, Inga (transcript, 2016)
Transcultural art education enables both a view of the self and the other. In doing so, it develops the special educational potential of art for members of a transcultural society. Providing the first systematic reflection on the hybrid state of contemporary society and taking into account art, cultural, and education studies, Inga Eremjan's foundational theoretical basis of transcultural art education illustrates how innovative forms of art education make transcultural processes possible. Eremjan shows how aesthetic-artistic practice and aesthetic experiences are central to this, because they open new perspectives on ways of thinking and acting, thereby supporting the self-determined participation of the subject.